The knowledge value chain as an SME innovation policy instrument framework: an analytical exploration of SMEs public innovation support in OECD countries. (1st January 2012) - Halilem, Norrin; Bertrand, Catherine; Cloutier, Jean Samuel; Landry, Réjean; Amara, Nabil
Innovation policy instruments in OECD countries are developed from different streams of policies related to the suppliers and the users of knowledge. They are also integrated into different levels of implementation (supranational, national, regional and local). Such complexity leads policy actors and stakeholders to experience a lack of coordination in their innovation efforts. This paper, based on a broad cross-country analysis of 844 innovation policy instruments implemented in 27 OECD countries, aims to contribute to the advancement of knowledge on this issue by: 1 validating a conceptual framework as a tool of policy instrument coordination 2 conducting an innovation policy instrument framework based both on the conceptual framework and a on diversity of instruments. The innovation policy instrument framework has been devised to be used as a roadmap to link innovation policy instruments and innovation functions.